Sex worker health outcomes in high-income countries of varied regulatory environments: A systematic review - McCann, Jessica; Crawford, Gemma; Hallett, Jonathan (MDPI, 2021)
There is significant debate regarding the regulation of the sex industry, with a complex range of cultural, political and social factors influencing regulatory models which vary considerably between and within countries. This systematic review examined the available evidence on the relationship between different approaches to sex industry regulation in high-income countries, and associated effects on sex worker health status. Objectives included identification of sex worker health outcomes, including sexual health, substance use and experience of stigma and violence. A search was performed electronically in eight scholarly databases which yielded 95 articles which met the criteria for inclusion. Findings suggested that sex workers in legalised and decriminalized countries demonstrated greater health outcomes, including awareness of health conditions and risk factors.